The Effect of Discovery Learning Model Based on Augmented Reality Media on Students' Critical Thinking Skills - Muh Tubagus Naufal Fahmi Tubagus; Suwardi; Choirul Anwar; Mildrett de Fatima Jalane (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aims to examine the effect of the DINAR (Discovery Learning based on Augmented Reality) model on the critical thinking skills of grade V Madrasah Ibtidaiyah students on the material of human respiratory organs. The method used was quasi-experimental with a non-equivalent control group design, involving 48 students divided into experimental (DINAR learning) and control (conventional method) groups. This research was conducted at MIS Raudlatul Mutaallimin, Pakis, Bringin District, Semarang Regency. Data were collected through critical thinking tests based on analysis, evaluation, and inference indicators, and analyzed using parametric statistical tests (Independent Sample T-Test) and N-Gain. The results showed a significant increase in the experimental group with an average posttest of 156.8 (versus 133.2 in the control). The T-Test produced a value of t(46) = -5.836 (p = 0.000), indicating a highly significant difference. N-Gain analysis reinforced these findings with an effectiveness score of 57.49% (moderately effective) in the experiment, while the control only reached 38.52% (less effective). The integration of Augmented Reality in Discovery Learning facilitates 3D visualization of respiratory organs, allowing students to explore concepts interactively and build independent understanding. This finding is in line with Bruner's theory of constructivism, asserting that a combination of immersive technology and explorative approaches effectively improves critical thinking skills. This study recommends the adoption of the DINAR model in science learning, particularly for abstract materials, as well as teacher training in AR-based media development.